TUBA1C: a potential biomarker for Type II Diabetes Mellitus (T2D) associated cancer - Eyupoglu, Erol; Eyupoglu, Havva Ozgen; Tuzmen, Sukru (Springernature, 2024)
[Abstract Not Available]
56th Annual Conference of the European-Society-of-Human-Genetics (ESHG) -- JUN 10-13, 2023 -- Glasgow, SCOTLAND